Personalisasi Pemasaran Email dalam Meningkatkan Program Loyalitas: Sebuah Konsep Komunikasi Pemasaran - Endang Kustami; Enggar Sulistiyono (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine the interaction between email marketing in the loyalty program by looking at the reactions of program members to emails sent. Email marketing, as part of a marketing strategy plays an important role in achieving maximum profit in business practices. However, how to operate personalized email marketing is a challenge for companies. A good strategy needs to be formed to improve marketing messages that can convince consumers through consumer behavior in loyalty programs. The concept offered is to use theory construal by building goal distance and the appeal of marketing messages (cognitively emotional) in email marketing. This research model uses email campaign samples from Indonesian airline companies taken during the period August - November 2022. The analysis method uses Panel Logit and Binomial Model Regression. The findings explain that there is a reciprocal and significant relationship between the distance of the message and the attractiveness of the message to the loyalty enhancement program. It was concluded that there was a significant relationship when the position of the target distance was at a 'large' level, so that cognitive appeal had a more persuasive impact than emotional appeal; so that an abstract framing message will have a more positive impact that effectively affects the level of achievement of the goal distance compared to a concrete appeal. Research has also found that when members/customers are close to their goals, emotional appeals have a more effective effect than concrete messages.